2018
DOI: 10.1007/s00402-018-2880-6
|View full text |Cite
|
Sign up to set email alerts
|

Tibial tunnel placement in anatomic anterior cruciate ligament reconstruction: a comparison study of outcomes between patient-specific drill template versus conventional arthroscopic techniques

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…During anterior cruciate ligament (ACL) reconstruction, the tibial footprint of the ACL could be seen easily without sacrificing the remnant ACL. 8 However, the ACL footprint of the femoral side is difficult to visualize using anterior arthroscopic portal without sacrificing the remnant ACL because of the blockage caused by the remnant of the ACL or the ridge of medial wall of the lateral femoral condyle. [9][10][11][12] Therefore, techniques are being used to attain both aims such as posterolateral (PL) viewing with a 70-degree scope and transseptal portal viewing.…”
mentioning
confidence: 99%
“…During anterior cruciate ligament (ACL) reconstruction, the tibial footprint of the ACL could be seen easily without sacrificing the remnant ACL. 8 However, the ACL footprint of the femoral side is difficult to visualize using anterior arthroscopic portal without sacrificing the remnant ACL because of the blockage caused by the remnant of the ACL or the ridge of medial wall of the lateral femoral condyle. [9][10][11][12] Therefore, techniques are being used to attain both aims such as posterolateral (PL) viewing with a 70-degree scope and transseptal portal viewing.…”
mentioning
confidence: 99%
“…It should assist minimally invasive temporomandibular joint arthrocentesis or arthroscopy to combine the potential advantages of these novel techniques and first clinical results are presented. This is the first known report of template-guided therapy in the TMJ other than the use of a cutting guide for tumor resection [10] and one of the first considering joint surgery besides arthroplasty resection guides [11].…”
Section: Introductionmentioning
confidence: 99%
“…The age of participants ranged from 14 to 54 years (391 patients) [1, 7, 12, 20, 43, 59] and follow‐up ranged from 12 to 60 months (775 patients) [1, 7, 12, 14, 20, 22, 27, 30, 31, 43, 59]. Three studies used computer‐assisted fluoroscopic navigation (142 patients) [7, 22, 27], 1 study used intraoperative fluoroscopy (60 patients) [1], 2 studies used personalized 3D‐printed drill guides following pre‐operative imaging (119 patients) [30, 59], and 5 studies used image‐free computer‐assisted navigation systems (454 patients) [12, 14, 20, 31, 43]. One study performed double‐bundle ACL reconstruction (60 patients) [1] and 1 study had a double‐bundle (DB) group in addition to its single‐bundle (SB) group in the technology‐assisted surgery group (55 patients, 37 patients excluding the DB group) [27].…”
Section: Resultsmentioning
confidence: 99%
“…One study (209 patients) demonstrated a signiicant increase in cost associated with use of computer-assisted navigation systems (mean 1158€ or approximately $1269 USD) versus conventional surgery (mean 704€ or approximately $771 USD) [31]. Of the two studies using 3D-printed templates, production costs ranging from $10 to $42 USD (approximately 9.1 € to 38.2 €) were cited [30,59]. Fig.…”
Section: Operative Length and Costmentioning
confidence: 99%